2016
DOI: 10.3389/fpls.2015.01183
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Brassica rapa Near-Isogenic Lines Carrying Clubroot-Resistant and –Susceptible Alleles in Response to Plasmodiophora brassicae during Early Infection

Abstract: Although Plasmodiophora brassicae is one of the most common pathogens worldwide, the causal agent of clubroot disease in Brassica crops, resistance mechanisms to it are still only poorly understood. To study the early defense response induced by P. brassicae infection, a global transcriptome profiling of the roots of two near-isogenic lines (NILs) of clubroot-resistant (CR BJN3-2) and clubroot-susceptible (BJN3-2) Chinese cabbage (Brassica rapa) was performed by RNA-seq. Among the 42,730 unique genes mapped to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
100
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 70 publications
15
100
2
Order By: Relevance
“…Microscopic observations revealed that root–hair infection (7 DAI) and cortical infection (14 DAI) were both present in B2013 and 90196 ( Figure 1 ). This finding was not in agreement with previous studies (Feng et al, 2013; Chen et al, 2016), in which secondary infection did not occur in resistant lines, possibly due to qualitative resistance under single-gene control.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Microscopic observations revealed that root–hair infection (7 DAI) and cortical infection (14 DAI) were both present in B2013 and 90196 ( Figure 1 ). This finding was not in agreement with previous studies (Feng et al, 2013; Chen et al, 2016), in which secondary infection did not occur in resistant lines, possibly due to qualitative resistance under single-gene control.…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed that the JA pathway was weakly activated in the resistant genotype but strongly induced in the susceptible genotype, in agreement with results reported for Arabidopsis by Lemarié et al (2015). Chen et al (2016) also demonstrated that the SA signaling pathway, but not the JA/ET signaling pathway, played a critical role in B. rapa resistance to P. brassicae infection. Jubault et al (2013) also found that both the SA and ET pathways were induced during the partial resistance response, whereas the JA pathway was repressed.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations